Internet-based information and foreign direct investment (FDI) location decision making: An information cost perspective - Kachwamba, Muhajir; Sæbø, Øystein (Acadenic journals, 2024)
A research article submitted to the African Journal of Business Management Vol.6 (20), pp. 6137-6150, 23 May, 2012